Restoration of Guyton´s diagram for regulation of the circulation as a basis for quantitative physiological model development - Kofránek, J; Rusz, J (Physiological research, 2010)
We present the current state of complex circulatory dynamics model development based on Guyton's famous diagram. The aim is to provide an open-source model that will allow the simulation of a number of pathological conditions on a virtual patient including cardiac, respiratory, and kidney failure. The model will also simulate the therapeutic influence of various drugs, infusions of electrolytes, blood transfusion, etc. As a current result of implementation, we describe a core model of human physiology targeting the systemic circulation, arterial pressure and body fluid regulation, including short- and long-term regulations. The model can be used for educational purposes and general reflection on physiological regulation in pathogenesis of various diseases.
Keywords: Systems Biology; tělesné tekutiny; Models, Cardiovascular; modely kardiovaskulární; Blood Circulation; Blood Pressure; Body Fluids; Humans; krevní oběh; krevní tlak; Computer Simulation; systémová biologie; lidé; počítačová simulace